Spatio-Temporal Analysis of Urban Land Use Changes in Abeli District, Kendari City - Nur Rahmayani; Anita Indriasary; Noor Husna Khairisa (Universitas Halu Oleo, 2024)
Urban areas, with their dynamic activities, continually undergo development, leading to changes in land use, as observed in the Abeli District, Kendari City. This study aims to: (1) Analyze land use in 2012 and 2022 in the Abeli District; (2) Identify the land use changes that occurred between 2012 and 2022 in the Abeli District. This research utilizes Google Earth satellite imagery data, analyzed through on-screen digitization and overlay methods. The findings reveal that: (1) There are nine land use categories: public service areas, commercial areas, industrial zones, open land, residential areas, agricultural land, green spaces, transportation infrastructure, and water bodies. In 2012, the largest land use category was green space, covering 1,166.13 hectares, followed by residential areas at 102,55 hectares. The smallest categories were commercial areas at 9,75 hectares and public service areas at 6,80 hectares. In 2022, green space remained a significant land use category at 132,98 hectares, alongside residential areas, also at 132,98 hectares, while the smallest categories were water bodies at 11,84 hectares and public service areas at 7,24 hectares; (2) The most significant land use change from 2012 to 2022 was an increase in residential areas by 30,43 hectares and a reduction in green space by 46,12 hectares.